Modern weapons and military equipment for issue 3-2017 - Jevtić, Miloš M. (Vojnotehnički glasnik / Military Technical Courier, 2017)
Successfully implemented "Čelik 2017":About the details of the dynamic display and the tactical-technical assembly within the complex of the "Nikinci" Test Center, on the occasion of the celebration of the Army Day of Serbia, Victory Day and Europe Day.